Bilateral Hemophthalmus — the First Symptom of Behcet’s Disease (Clinical Case) - O. Yu. Yatsenko; O. S. Velibekova; A. I. Samoilenko; I. M. Tikhonova; I. G. Burdenko; E. N. Panina (Oftalʹmologiâ, 2016)
Behcet’s disease (BD) — a systemic chronic idiopathic inflammatory recurrent disease of unknown etiology. The development of the disease involve a combination of various factors, among them the most important is genetic and infectious. Eye lesion is one of the most frequent and severe symptoms of Behcet’s disease. According to the literature, eye lesion appears in 54–90% cases. There are several types of Behcet’s disease: the front, posterior and panuveitis, retinal vasculitis, occlusion of the branches of the central retinal vein, episcleritis, scleritis, keratitis, anterior ischemic neuropathy, paralysis of the extraocular muscles, swelling of the macula. In 95% cases the process is bilateral, but the clinical signs are often asymmetrical. Ocular pathology usually develops after 2–3 years the onset of symptoms BD. We havn’t met in the literature any case of Behcet’s disease, which has begun with hemophthalmia. Taking all these points together it seems to us interesting to present a clinical case of Behcet’s disease which has debuted with a bilateral hemophthalmus. This article describes a clinical case of Behcet’s disease in a patient of 38 years old. The interest of this observation is caused by feature of the appearance of clinical symptoms. Bilateral hemophthalmus has originally appeared, twice (in 2013 and 2014) and has been treated. During the next hospitalization the treatment has produced the positive effect was less  pronounced. After that, patient has undergone bilateral vitrectomy (2014). In April 2015 there were recurrent mouth ulcers, and 3 months later groin ulcers has appeared, pain in the joints. The ophthalmologist examination has shown commenmorative signs of left uveitis. The patient was counseled at the Institute of Rheumatology, where were determined the diagnosis of Behcet’s disease.This paper shows the clinical data and the results of additional tests (OCT, fluorescein angiography, ultrasonography), the results of blood biochemical examination and immune status.